Recent Biomedical Approaches for Chitosan Based Materials as Drug Delivery Nanocarriers - Andreea Teodora Iacob; Florentina Geanina Lupascu; Maria Apotrosoaei; Ioana Mirela Vasincu; Roxana Georgiana Tauser; Dan Lupascu; Simona Eliza Giusca; Irina-Draga Caruntu; Lenuta Profire (MDPI AG, 2021)
In recent decades, drug delivery systems (DDSs) based on nanotechnology have been attracting substantial interest in the pharmaceutical field, especially those developed based on natural polymers such as chitosan, cellulose, starch, collagen, gelatin, alginate and elastin. Nanomaterials based on chitosan (CS) or chitosan derivatives are broadly investigated as promising nanocarriers due to their biodegradability, good biocompatibility, non-toxicity, low immunogenicity, great versatility and beneficial biological effects. CS, either alone or as composites, are suitable substrates in the fabrication of different types of products like hydrogels, membranes, beads, porous foams, nanoparticles, in-situ gel, microparticles, sponges and nanofibers/scaffolds. Currently, the CS based nanocarriers are intensely studied as controlled and targeted drug release systems for different drugs (anti-inflammatory, antibiotic, anticancer etc.) as well as for proteins/peptides, growth factors, vaccines, small DNA (DNAs) and short interfering RNA (siRNA). This review targets the latest biomedical approaches for CS based nanocarriers such as nanoparticles (NPs) nanofibers (NFs), nanogels (NGs) and chitosan coated liposomes (LPs) and their potential applications for medical and pharmaceutical fields. The advantages and challenges of reviewed CS based nanocarriers for different routes of administration (oral, transmucosal, pulmonary and transdermal) with reference to classical formulations are also emphasized.